An Emergent Entity: Indolent Mucormycosis of the Paranasal Sinuses. A Multicenter Study - Celis-Aguilar, Erika; Burgos-Páez, Alan; Villanueva-Ramos, Nadia; Solórzano-Barrón, José; De La Mora-Fernández, Alma; Manjarrez-Velázquez, Juan; Verdiales-Lugo, Sergio; Escobar-Aispuro, Lucero; Becerril, Perla; Valdez-Flores, Ana; Merino-Ramírez, Francisco Javier; Caballero-Rodríguez, Carmen Beatriz (International Archives of Otorhinolaryngology, 2019)
Introduction Indolent or chronic mucormycosis is a rare entity that affects both immunosuppressed and immunocompetent individuals. Additionally, its clinical evolution is nonspecific and there is no standardized treatment for this condition.Objective To describe the clinical characteristics and management of patients with indolent mucormycosis.Methods In the project of study with chart review in the Interinstitutional secondary care centers, patients with evidence of indolent mucormycosis, defined as pathological confirmation of nasal/paranasal sinus mucormycosis for more than 1 month, were included. All patients underwent complete laboratory workup, imaging studies, surgical treatment and adequate follow-up. No evidence of disease status was defined when patient had subsequent biopsies with no evidence of mucormycosis.Results We included seven patients, three female and four male subjects. The mean age was 53.14 years. Four patients were immunosuppressed and three immunocompetent. Among the immunosuppressed patients three had diabetes and one had dermatomyositis. The symptoms were nonspecific: facial pain/headache, mucoid discharge and cacosmia were the ones most frequently reported. Maxillary sinus involvement was present in all patients. Two immunosuppressed subjects received amphotericin. Posaconazole was the only treatment in one immunosuppressed patient. All immunocompetent patients had single paranasal sinus disease and received only surgical treatment. All patients are alive and free of disease.Conclusion Indolent mucormycosis is a new and emerging clinical entity in immunosuppressed and immunocompetent patients. Single paranasal sinus disease is a frequent presentation and should not be overlooked as a differential diagnosis in these patients. Immunocompetent patients should only be treated surgically.
Keywords: mucormycosis; mucorales; paranasal sinuses; sinusitis; mycoses; chronic mucormycosis